2008
DOI: 10.2337/db07-1124
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Incretin Concentrations in Subjects With Normal, Impaired, and Diabetic Glucose Tolerance

Abstract: OBJECTIVE-Defects in glucagon-like peptide 1 (GLP-1) secretion have been reported in some patients with type 2 diabetes after meal ingestion. We addressed the following questions: 1) Is the quantitative impairment in GLP-1 levels different after mixed meal or isolated glucose ingestion? 2) Which endogenous factors are associated with the concentrations of GLP-1? In particular, do elevated fasting glucose or glucagon levels diminish GLP-1 responses?RESEARCH DESIGN AND METHODS-Seventeen patients with mild type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
268
8
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(310 citation statements)
references
References 60 publications
(71 reference statements)
22
268
8
7
Order By: Relevance
“…Some recent studies have reported that the circulating GIP concentrations were associated with the development of diabetes in humans. 6,7) Although it is assumed that there are many reasons for the improvement of diabetes by the RS intake, and it needs to be investigated whether the repression of excessive GIP secretion can lead to the prevention/improvement of diabetes and the associated complications, the results of our current study support this notion.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Some recent studies have reported that the circulating GIP concentrations were associated with the development of diabetes in humans. 6,7) Although it is assumed that there are many reasons for the improvement of diabetes by the RS intake, and it needs to be investigated whether the repression of excessive GIP secretion can lead to the prevention/improvement of diabetes and the associated complications, the results of our current study support this notion.…”
supporting
confidence: 79%
“…Indeed, some studies have observed that the circulating GIP levels were higher in obese and diabetic subjects than in healthy subjects. [4][5][6][7] It is thus believed that repressing the excessive GIP and insulin secretion caused by delaying the digestion/absorption of carbohydrates is important for preventing/improving such diseases. Several human studies have already shown that the postprandial induction of circulating GIP was repressed by a simultaneous intake of acarbose, [8][9][10] an inhibitor of disaccharidases in the small intestine, a soluble fiber guar gum 11) and resistant starch (RS), 12) which consists of an autoclaved high-amylose starch, is known to undergo digestion slowly and has the characteristics of a dietary fiber.…”
mentioning
confidence: 99%
“…In particular, leptin stimulates GLP-1 secretion, and this effect was attenuated in subjects with leptin resistance (29), while glucagon correlated negatively with GLP-1 during OGTT in patients with T2DM. On the other hand, no relationships between the parameters of glucose control, insulin sensitivity, and secretion with GLP-1 levels have been found (30).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, heterogeneity was apparent between studies that used mixed meal (lower GLP-1 among diabetes) and oral glucose load (higher GLP-1). Studies that directly compared GLP-1 responses following oral glucose vs mixed meal are scarce and the available studies did not find an altered GLP-1 response after both interventions among diabetic patients (7). GIP responses were found to be reduced (8), increased (7,9), but mostly unchanged in patients with diabetes (10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%